Analysis Of Android Based Mobile Blocking Application Design Using Mit App Inventor - Riska Robianto (LLDIKTI Wilayah X, 2020)
Mobile phone or cellphone is a device that can’t be separated and left by anyone. Every day, almost every chance we see someone always holding a cellphone in every activity, whether working with full cell phone support or just mere communication needs. However, for mobile users who are busy, driving, in worship or in other circumstances, often get incoming calls or SMS that are not cold. This study presents a solution to politely block or reject incoming calls or reply automatically to SMS. The solution is in the form of developing an Android-based cell phone blocking application which becomes a backroud process to handle each event and then automatically processes it by the application. The selection of the Android platform for mobile devices because the operating system is based on the Linux kernel which is designed for mobile devices touch screen and with open source support makes it easy for application developers to freely modify and distribute in a well-known market place. From a series of experiments and analysis of applications developed, the overall application can work well with a fast response supported by simple operation methods and designs that are easy to understand so the user is greatly helpful.